Maintenance of Primary Human Colorectal Cancer Microenvironment Using a Perfusion Bioreactor‐Based 3D Culture System. Issue 4 (7th March 2019) - Manfredonia, Celeste; Muraro, Manuele G.; Hirt, Christian; Mele, Valentina; Governa, Valeria; Papadimitropoulos, Adam; Däster, Silvio; Soysal, Savas D.; Droeser, Raoul A.; Mechera, Robert; Oertli, Daniel; Rosso, Raffaele; et al.
Abstract: Colorectal cancer (CRC) is a leading cause of cancer‐related death. Conventional chemotherapeutic regimens have limited success rates, and a major challenge for the development of novel therapies is the lack of adequate in vitro models. Nonmalignant mesenchymal and immune cells of the tumor microenvironment (TME) are known to critically affect CRC progression and drug responsiveness. However, tumor drug sensitivity is still evaluated on systems, such as cell monolayers, spheroids, or tumor xenografts, which typically neglect the original TME. Here, it is investigated whether a bioreactor‐based 3D culture system can preserve the main TME cellular components in primary CRC samples. Freshly excised CRC fragments are inserted between two collagen scaffolds in a "sandwich‐like" format and cultured under static or perfused conditions up to 3 d. Perfused cultures maintain tumor tissue architecture and densities of proliferating tumor cells to significantly higher extents than static cultures. Stromal and immune cells are also preserved and fully viable, as indicated by their responsiveness to microenvironmental stimuli. Importantly, perfusion‐based cultures prove suitable for testing the sensitivity of primary tumor cells to chemotherapies currently in use for CRC. Perfusion‐based culture of primary CRC specimens recapitulates TME key features and may allow assessment of tumor drug response in a patient‐specific context. Abstract : In this work, the authors establish a model of human colorectal cancer tissue by culturing primary, freshly excised patient material in a perfusion‐based bioreactor. The cultured tumor tissues preserve structural features and the diverse cellular composition of fresh specimens, ultimately allowing to test tumor responsiveness to chemotherapy in a more physiological, patient‐specific context.